The Research Project : How to write it - Berry, Ralph, 1931-; Berry, Ralph, 1931- (London : Routledge, 1994)
An essential introduction for students just starting project work. Guides students through choosing a topic, using the library, taking notes, writing cross-references and bibliographies.
Previous ed. : published as How to write a research paper. Oxford : Pergamon, 1986.
Keywords: Report writing